The dynamics of schools of thought in the sociology of law: Exploring the relevance in the formation of citizenship values in contemporary Indonesia - Khaitsa Zahira (Universitas Negeri Yogyakarta, 2025)
This study explores the evolution of legal thought within the sociology of law and its relevance to the formation of citizenship values in contemporary Indonesia. Drawing from Soerjono Soekanto's foundational work, Pokok-Pokok Sosiologi Hukum, the research emphasizes the significance of understanding law as a social institution influenced by cultural and societal dynamics. Robert W. Hefner's Islam and Citizenship in Indonesia provides insights into how Islamic traditions intersect with democratic principles, shaping inclusive notions of citizenship in the Indonesian context. Additionally, the study considers the impact of globalization on citizenship policies, referencing Antikowati et al.'s analysis of dual citizenship demands in Indonesia. Through a sociological lens, the research underscores the interplay between legal frameworks, cultural values, and societal changes in shaping contemporary Indonesian citizenship.